Meningkatkan Kemampuan Anak Dalam Membaca dengan Menggunakan Kartu Gambar di TK Negeri Pembina Lawe Pakam - Malem Skd, Seroja; Nunzairina, Nunzairina (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
This research aims to find out how to improve children's reading skills by using picture cards at the Pembina Lawe Pakam State Kindergarten, Southeast Aceh. The data collection technique used in this research is observation of children and teachers. Apart from observations, researchers conducted in-depth interviews with children and teachers regarding improving children's reading skills on picture cards at the Lawe Pakam State Kindergarten. The achievement level of improving reading comprehension for early childhood in the Lawe Pakam State Kindergarten with picture cards increases or not if the ability score reaches 85% or more. The model used is the Kemmis and Mc Taggart model which consists of planning, implementation, observation and reflection. The results of this research show that. Keywords: Improving, Reading Ability, and Drawing Cards